2021
DOI: 10.1101/2021.06.11.21258735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quarantine and testing strategies to reduce transmission risk from imported SARS-CoV-2 infections: a global modelling study

Abstract: Background Many countries require incoming air travellers to quarantine on arrival and/or undergo testing to limit importation of SARS-CoV-2. Methods We developed mathematical models of SARS-CoV-2 viral load trajectories over the course of infection to assess the effectiveness of quarantine and testing strategies. We consider the use of Polymerase Chain Reaction (PCR) and lateral flow testing (LFT) both pre-flight, to reduce the number of infectious arrivals and when exiting quarantine, and daily testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Many countries require travellers to present proof of a negative antigenic or molecular test result 72 h ahead of a flight, to quarantine after arrival, and to test negative with either a molecular test or Ag-RDT for release. 92 Although models of strategies to mitigate the importation risk have been published, 93 , 94 , 95 there is no global or regional consensus on any one risk-reduction strategy.…”
Section: Use Of Diagnostics In Containment Of Pandemics and Outbreaksmentioning
confidence: 99%
“…Many countries require travellers to present proof of a negative antigenic or molecular test result 72 h ahead of a flight, to quarantine after arrival, and to test negative with either a molecular test or Ag-RDT for release. 92 Although models of strategies to mitigate the importation risk have been published, 93 , 94 , 95 there is no global or regional consensus on any one risk-reduction strategy.…”
Section: Use Of Diagnostics In Containment Of Pandemics and Outbreaksmentioning
confidence: 99%
“…This formulation assumes that all isolated individuals transmit at a reduced rate However, we expect average model outputs to be very similar if we instead assumed that a fraction of isolated individuals transmit at the same rate as a non-isolated individual and a fraction do not transmit at all ( Quilty et al, 2021 ). Individuals that develop symptoms after arrival seek a test with probability 80%.…”
Section: Methodsmentioning
confidence: 99%
“…The modelling approach is similar to that of ( Quilty et al, 2021 ), which estimated the reduction in transmission potential from a range of traveller interventions. The model of ( Quilty et al, 2021 ) modelled individual heterogeneity in viral load trajectories and assumed that the transmission rate and the probability of testing positive are both functions of the viral load. This requires that there is a unique one-to-one mapping between the transmission rate at time and the probability of testing positive at time .…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggested that there were effective alternative strategies with shorter quarantine and testing to prevent COVID-19 surges due to the importation of infected people as an effective replacement of the travel ban. [37]. The authors concluded that preflight antigen testing, with a five-day quarantine after entry into the country and an additional antigen test to exit quarantine, might prevent most COVID-19 transmissions, while reducing the duration of quarantine.…”
Section: Prevention Sars-cov-2 Importation At Different Stages Of The...mentioning
confidence: 99%